Communication between median and musculocutaneous nerve at the level of cubital fossa - A case report - Clarissa Ann Elisabeth Gelmi; Francesca Alice Pedrini; Matteo Fermi; Giulia Adalgisa Mariani; Lucio Ildebrando Cocco; Anna Maria Billi (Elsevier, 2018)
The anatomical variations of the brachial plexus are important to be reported, in order to avoid their damage during the upper-limb surgical procedures. Despite of the frequent documented abnormalities in the pathway of the musculocutaneous and the median nerves, the anatomical variation accurately described in the present case is unusual to see: it does not perfectly come under any of the classifications proposed in literature. During the dissection of the right brachial plexus in an old male Caucasian cadaver a communicating branch between the musculocutaneous nerve and the median nerve was observed. Proximally It originated by the musculocutaneous nerve, after its perforation of the coracobrachialis muscle; distally it joined the median nerve only at the level of the cubital fossa. The musculocutaneous nerve and the median nerve maintained their normal courses, supplying all the collateral and terminal branches. In the same limb an atrophied short head of the biceps brachii muscle was also seen. Keywords: Median nerve, Musculocutaneous nerve, Communicating branch, Brachial plexus, Variation